The Safe Drinking Water and Clean Water Acts: A Small Community View - Levy, Steve (Maine Policy Review, 1992)
The Safe Drinking Water Act of 1986 and the Clean Water Act Amendments of 1991 present significant financial and technical challenges to municipalities in Maine and other states as they struggle to meet compliance standards. Steve Levy, executive director of the Maine Rural Water Association, offers a view of the effects of these requirements on rural communities.